The maximal lactate steady state in elite endurance athletes - Hoogeveen, A. R.; Hoogsteen, J.; Schep, G. (Japanese Journal of Physiology, 1997)
The upper limit of blood lactate resulting in a lactate steady state during prolonged exercise is called the maximal lactate steady state (MLSS). The purpose of this study was to investigate the lactate response to steady-state exercise during a field test in elite endurance athletes. Plasma lactate levels were assessed in 13 elite triathletes and 13 elite cyclists (mean +/- SD; age 23.7 +/- 5.1 yr; HT 180.2 +/- 6.3 cm; WT 70.3 +/- 5.9 kg; VO2 max 68 +/- 3.7 ml/min/kg) during a 40 km-long time trial on a bicycle (4 km course x 10 laps). The steady state was demonstrated by monitoring the heart rate and timing every course run. The lactate levels were expected to correspond to MLSS. The mean level of lactate during the time trial was 7.4 +/- 2.5 mmol/l. Five athletes maintained plasma lactate levels which exceeded 10 mmol/l or more for almost 1 h. The large value of individual variability was conspicuous (range 3.2-12.2 mmol/l). These values exceeded all previous reported levels for MLSS from other investigators. Our observations are important in sport medical practice since the different lactate responses to exercise are used as parameters in training management.